Evaluation of a Naturally-derived Deflocculant (Terminalia Chebula) in Bentonite Dispersions - Jalal Neshat (Iranian Journal of Oil & Gas Science and Technology, 2016)
The unwanted addition of salt to drilling causes flocculation which has an adverse effect on mud rheological properties. To treat the flocculated mud chemical, deflocculants are commonly used; however, their disadvantages such as negative environmental effects, lower tolerance to contamination, and toxicity motivated scientists to search for effective additives. Using plant derived additives instead of commercial additives could help resolve the mentioned weaknesses, because they are nontoxic, cheap, easily accessible, and act multi-functional. In this paper the effect of black myrobalan rheological properties of flocculated bentonite mud was investigated and its performance was compared with chrome lignosulfonate (CLS). Rheological and filtration tests were conducted and properties such as plastic viscosity, yield point, gel strength, thixotropy, and apparent viscosity were calculated. It was perceived that by increasing black myrobalan concentration to 0.6 wt.%, rheological parameters and filtration loss decreased by 50% and 66.3% respectively, but they increased at higher concentrations, which indicated that black myrobalan acted as a deflocculant up to 0.6 wt.%. The deflocculation behavior of black myrobalan at low concentrations is attributed to ellagitannic acid and tannic acid. The comparison of the enactment of black myrobalan with chrome lignosulfonate showed that black myrobalan had a stronger decreasing effect on the rheological parameters and filtration compared to CLS.